The FAKTOR PENENTU PRODUKSI KELAPA SAWIT RAKYAT DI PROVINSI RIAU - Ismiasih Ismiasih; Helmi Afroda (Jurnal Penelitian Pertanian Terapan, 2023)
Oil palm plantations have a strategic role as a contributor to the country's foreign exchange and as a provider of employment opportunities for people in Indonesia. Palm oil production in Indonesia is still dominated by large private plantations, but smallholder plantations are increasingly playing an important role in palm oil production. However, the problem is that the production of crude palm oil (CPO) by smallholder plantations has large variations, and is below plantation standards. This study aims to determine the factors that influence smallholder oil palm production in Riau Province. The data collected is secondary data based on the results of the 2013 agricultural census by the Central Statistics Agency (BPS). The number of samples as many as 4,038 farmers, spread across the Riau Province. The method of determining the research location was chosen purposively, namely Riau Province as the research area with the consideration that this area is the largest palm oil producing center in Indonesia. The analytical method used to determine the factors that affect oil palm production is the Cobb Dauglash production function model which is estimated by the OLS (Ordinary least square) method. The results showed that the factors that influenced the production of smallholder palm oil in Riau Province were the number of plants, plant age, urea fertilizer, SP36 fertilizer, NPK fertilizer, organic fertilizer, number of workers,  members of the cooperative and  partnership participants.